Multifunction bookshelf / Mohmamad Uzair Hafiz Abdul Fatah - Abdul Fatah, Mohmamad Uzair Hafiz (2022)
Nowadays there is a lot designs of the bookshelf people can get from the furniture store. Even though there is a lot of designs, it is only used to store books and nothing else. People always looking the place for a seat to read book comfortably. In libraries, chairs and tables are provided because the libraries are spacious, but it is different with the room with small space.